Water Pricing with Household Surveys: A Study of Acceptability and Willingness to Pay in Chongqing, China - Wang, Hua (2012)
In determining domestic water prices, policy makers frequently need to use demand-side information rather than only rely on supply-side data as previously did, and household surveys are often conducted to collect information on the demand side. This paper presents a multiple bounded discrete choice (MBDC) survey model for collecting information about acceptability of different water prices by different types of households and estimating households' willingness to pay for water service improvement. The results obtained from MBDC surveys can be directly utilized in the development of water pricing and subsidy policies. An empirical MBDC study is conducted in Chongqing, China, where domestic water service quality was seriously inadequate, but financial resources were insufficient to improve the service quality. With a survey of 1500 households in five suburban districts in Chongqing Municipality, this study shows that a significant increase in water price is economically feasible as long as the poorest households are properly subsidized. The analysis also indicates that the order in which hypothetical prices are presented to the respondents with the MBDC method can systematically affect the answers and should be taken into account when designing such survey instruments.